Optimization Flotation Process Using Two Types of Collectors at PT. Florrea Indonesia - Triandika, Taufan; Sukamto, Untung; Sudaryanto, Sudaryanto; Amalia, Yasmina; Allya Zulfa Suratinoyo, Zahna (Journal of Metallurgical Engineering and Processing Technology, 2024)
The tailings slurry used in this research originated from company X in Kuala Lipis, Pahang, Malaysia. The primary objective of this study is to determine the percentage of recovery, concentrate content, and Au concentration ratio in the tailings slurry. The research employs a quantitative method involving flotation testing. The flotation process involved two sets of experiments: one without the FX2 collector (tests 1 and 2) and another using both the F7042W and FX2 collectors (tests 3 and 4). dxThe research findings revealed that the percentage of Au recovery in single-collector flotation using FX2 (test 1) was 56.47%, with a concentration ratio of 19.78. In test 2, it was 52.59%, with a mass concentration ratio of 21.57. Meanwhile, the percentage of Au recovery in dual-collector flotation using F7042W and FX2 (test 3) was 68.77%, with a concentration ratio of 16.55, and in test 4, it was 69.45%, with a concentration ratio of 16.93. Based on the results of this research, it can be concluded that the flotation process employing two collectors, namely F7042W and FX2, as investigated in this study, was successful because percent recovery, concentration ratio, and Au content in the concentrate compared to single collector flotation.